Crystal structure of bis(2-methoxy-6-((Z)-(p-tolylimino)methyl)phenoxy)palladium - Kassim K.; Kahar M.A.M.; Yamin B.M.; Manan M.A.F.A.; Yusof M.S.M. (Japan Society for Analytical Chemistry, 2024)
Indexed by WOS/ Scopus